THE AVOIDANT PERSONALITY DISORDER AS A VULNERABILITY FACTOR IN MIXED ANXIETY AND DEPRESSIVE DISORDER: A CASE REPORT - Jeanne Meilisa Sitopu; Elsy Emmily Gracia; Mirna Lidiya Yosefa Sinaga (Mandala Of Health, 2026)
Background: The prevalence of Avoidant Personality Disorder has been estimated at approximately 3.3%, with one study reporting a lifetime prevalence of 9.3% among women older than 25 years. Avoidant Personality Disorder is an enduring personality pattern characterized by social avoidance, feelings of inadequacy, and hypersensitivity to negative evaluation. These characteristics may function as psychological vulnerability factors for affective psychopathology, particularly Mixed Anxiety and Depressive Disorder. Methods: This study employed a qualitative descriptive case report approach. Data were obtained through comprehensive psychiatric history-taking, mental status examination, clinical observation, and psychometric assessment using the Hamilton Anxiety Rating Scale (HARS), Hamilton Depression Rating Scale (HDRS), Minnesota Multiphasic Personality Inventory-2 (MMPI-2), and Millon Clinical Multiaxial Inventory-IV (MCMI-IV). Diagnosis was established in accordance with the Indonesian Classification and Diagnostic Guidelines for Mental Disorders, Third Edition (PPDGJ III). Results: Mrs. RM, a 29-year-old woman, presented with complaints of anxiety, marked difficulty engaging in social interactions due to fear of rejection, impaired concentration, and difficulty initiating sleep, accompanied by palpitations, tremulousness, and cold extremities for the preceding three months. The patient experienced significant psychosocial stressors, including family dysfunction and marital relationship difficulties, which were exacerbated by underlying avoidant personality disorder pathology. Psychometric evaluation revealed moderate anxiety and depressive symptoms, while personality assessment demonstrated a persistent avoidant personality pattern. The patient was diagnosed with Mixed Anxiety and Depressive Disorder with comorbid Avoidant Personality Disorder. Clinical improvement was observed following treatment with fluoxetine 20 mg once daily, clobazam 10 mg once daily, supportive psychotherapy, and Cognitive Behavioral Therapy (CBT). Conclusion: Avoidant Personality Disorder served as a major vulnerability factor and enduring personality pattern contributing to the development and persistence of Mixed Anxiety and Depressive Disorder, thereby prolonging and complicating the therapeutic course. Appropriate psychotherapeutic intervention, particularly CBT, is therefore essential in the management of such cases.